2018
DOI: 10.1136/bcr-2018-224710
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of persistent distressing neuropsychiatric symptoms by clozapine in a patient suffering from dementia with Lewy bodies

Abstract: Dementia with Lewy bodies (DLB) is the second most common neurodegenerative dementia associated with poor prognosis and high carers' burden. Neuropsychiatric symptoms worsen this prognosis and are a high source of distress for service users and their carers. However, there is currently insufficient evidence to support the pharmacological and non-pharmacological management of these symptoms. Acetylcholinesterase inhibitors are the first-line pharmacological option, but challenging risky behaviours may persist d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This agrees with Harwood [37] who asserts that if treated in the wrong way, people with dementia are easily distressed, suffer complications and may be unnecessarily disabled. Also poor response after multiple treatment options in patients with dementia has been reported [38] even with adverse central effects especially when using opioid analgesic drugs [35]. At clinic level, the observed minimal visits to clinics are well understood and expected.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with Harwood [37] who asserts that if treated in the wrong way, people with dementia are easily distressed, suffer complications and may be unnecessarily disabled. Also poor response after multiple treatment options in patients with dementia has been reported [38] even with adverse central effects especially when using opioid analgesic drugs [35]. At clinic level, the observed minimal visits to clinics are well understood and expected.…”
Section: Discussionmentioning
confidence: 99%
“…As for reports on the use of clozapine in single cases of dementia, one 19 reports a schizophrenic patient with Korsakoff syndrome who could be discharged from a closed ward 4 weeks after starting clozapine at a higher dosage (450 mg/day), although this case should not be considered a typical dementia patient given the principal diagnosis of schizophrenia. Another report exists of a patient with DLB who was successfully treated with clozapine for hallucinations and agitation 29 . A more typical case is found of a 75‐year‐old demented man who was successfully treated for behavioural problems with clozapine at low doses, 18 twice failing to reduce the dose.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case report, clozapine was initiated as an adjunct to an acetylcholinesterase inhibitor resulting in complete remission of agitation and reduction in psychosis symptoms without impairing mood or behavior symptoms. 25 Valproic acid can be helpful as an adjunct to atypical antipsychotic medications such as quetiapine in managing agitation; however evidence for this is sparse. 26 Studies have shown reduction in concomitant psychoactive medications when valproic acid is used in acutely agitated patients.…”
Section: Discussionmentioning
confidence: 99%